Dissemination of Salmonella enteritidis by experimentally-infected pigeons - Albuquerque,ÁH (2013)
Two groups of domestic pigeons (Columba livia) were experimentally infected orally with doses of 9.5 x10(7) and 9.5 x10(9) CFU/mL (group A and B, respectively) of a Salmonella Enteritidis (SE) strain isolated from chickens. None of the used doses caused mortality of the inoculated birds; however, the pathogen was successfully recovered from the liver and spleen of group B birds on day 7 post-inoculation (dpi). Pathogen shedding, as evaluated through cloacal swabs, occurred in both groups until the 14th day of observation (p <0.05). Among all fecal samples collected from group B (n=4), three different birds shed the pathogen in their feces, out of which two were positive on 3 dpi and one on 7 dpi. The same number of fecal samples was evaluated in group A and only one bird shed the pathogen, on 7 and 14 dpi. The concentration of the microorganism in the feces was lower in group A than any sample from Group B. Salmonella Enteritidis isolated from chickens, when inoculated in pigeons, may be recovered from feces, cloacal swabs and organs, and these birds may contaminate poultry causing economic losses as well as posing a risk to the public health.